Pemodelan dan Simulasi Perambatan Panas dan Laju Aliran Udara Pada Mesin Penetas Telur Statis Menggunakan Computational Fluid Dynamics Software - Agus Mukhtar; Rifki Hermana; Oki Prio; Hisyam Ma’mun; Aan Burhanudin (CV. IRA PUBLISHING, 2023)
Egg incubators are devices designed to create optimal conditions for eggs to hatch into chicks. Several important factors that must be considered in the egg incubator include temperature, humidity and air flow rate in the egg incubator chamber. Simulation of heat propagation and airflow rate in the hatchery was carried out using CFD software. The simulation results of heat propagation with a heating source above the egg rack obtained a maximum temperature of 312oK or the equivalent of 38.85o C which is right below the heater while the lowest temperature is 311°K or the equivalent of 37.85°C which is in the corner of the hatchery. The simulation results of the air flow rate with an air flow velocity of 1m/s obtained that the egg incubator with a heating source above the egg rack has an air flow rate in the hatchery space that is evenly distributed throughout the room so that the air can reach all the eggs in the hatchery room with a level hatching success of 80.5%.